Low Range of Shoulders Horizontal Abduction Predisposes for Shoulder Pain in Competitive Young Swimmers - Cejudo, Antonio; Sánchez-Castillo, Sheila; Sainz de Baranda, Pilar; Gámez, Juan Carlos; Santonja-Medina, Fernando (Frontiers in Psychology, 2019)
The prevalence of shoulder pain (SP) among competitive swimmers is high, and may profoundly restrict their ability to compete. This prospective cohort study investigated the association between 3 blocks of performance factors (anthropometric characteristics, sport experience and training regimen) and the presence of SP. The aims of the present study were: (a): to determine the profile of shoulder flexibility in young swimmers, (b) to analyse whether a restricted range of movement (ROM) could be a predictor of subsequent SP in young swimmers. 24 competitive young swimmers were measured in the 2016 pre-season. Measures of passive maximal shoulder extension [SE], flexion [SF], horizontal abduction [SHAB], abduction [SAB], horizontal adduction [SHADD], external [SER] and internal [SIR] rotation ROMs were taken. SP was prospectively monitored during the subsequent season using questionnaires. The data was analysed via a binary logistic regression and ROC curves were calculated. At the follow-up, 16 swimmers (50%) had developed unilateral SP. Only reduced SHAB ROM was associated with SP (SP group 36.6º vs pain-free group 41.5º; p = 0.005, d= -0.96 [moderate effect sizes]). Using the coordinates of the curves, the angle of SHAB ROM that most accurately identified individuals at risk of developing SP was determined to be 39º (sensibility 0.656 and 0.375 specificity). Swimmers with limited ROM (≤ 39º) have 3.6 times higher risk of developing SP than swimmers with normal ROM (>39º). This study clearly shows that low range of SHAB is a risk factor for developing SP in competitive young swimmers. In the studied data, a SHAB range of 39º was found to be the most appropriate cut-off point for prognostic screening